2016
DOI: 10.21474/ijar01/2560
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multiple Sclerosis in Saudi Arabia

Abstract: This study aimed at detecting a rough estimation of the prevalence of multiple sclerosis among citizens of Saudi Arabia. Methodology:It is a cross sectional study purposed to estimate the prevalence of multiple sclerosis in KSA in 2016. It involved 633 individual from the society of Saudi Arabia. Results and conclusion:Most of the respondents (68.1%)were female, Also most of them (47.1%) aged between (20-24) , (94.5%) of them were Saudi national, the largest proportion of them (34.4%) live in the eastern regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…Few studies reported an association with familial MS while others did not. 6,27 Nonetheless, parental consanguinity in our study was significantly higher among the group of patients with positive family history (56.3%) compared to the group with negative family history (27.9%). These findings were consistent with other MS studies, which found that familial MS (FMS) patients were more likely than non-FMS patients to report PC, suggesting a potential role of consanguinity in familial MS. 6 In addition, among those with siblings affected, female siblings were found to be more affected than male siblings were.…”
Section: Resultscontrasting
confidence: 49%
“…Few studies reported an association with familial MS while others did not. 6,27 Nonetheless, parental consanguinity in our study was significantly higher among the group of patients with positive family history (56.3%) compared to the group with negative family history (27.9%). These findings were consistent with other MS studies, which found that familial MS (FMS) patients were more likely than non-FMS patients to report PC, suggesting a potential role of consanguinity in familial MS. 6 In addition, among those with siblings affected, female siblings were found to be more affected than male siblings were.…”
Section: Resultscontrasting
confidence: 49%
“…However, the percentage of patients with a family history of MS was 11.1% in that study. 20 Another study in Qatar found a positive family history in first and second degree relatives in 10.4% of MS patients. 21 In our study, 30% of the MS patients had a history of consanguineous marriages.…”
Section: Discussionmentioning
confidence: 98%